Advanced operations research - Bhunia, A.K.; Sahoo, L. (New Delhi: Asian Books Pvt. Ltd., 2011)
This book has been intended to introduce the fundamental and advanced concepts of Operations Research. This book is based on Operation Research related courses for undergraduate and post graduate students of Mathematics, Statistics, Engineering, Computer Applications of universities as well as for the researchers working on different areas of Operations Research. The main objective of the book is to acquaint and familiarize the subject to the readers. In this book some advanced topics have also been included for the researchers in the area of the Operations Research.
Mathematical preliminaries -- Introduction of OR -- Linear programming problem -- Convex set and properties -- Simplex method -- Duality theory -- Transportation problems -- Assignment problem -- Revised simplex method -- Dual simplex method -- Bounded variable technique -- Post optimality analysis in L.P.P. -- Integer programming -- Sequencing -- Project management -- Reliability -- Inventory control theory -- Queueing theory -- Dynamic programming -- Theory of game -- Replacement of items -- Information theory -- Flow in networks
Keywords: Operations Research